What determines the extent of fiscal decentralization ? : The Russian paradox - Frejnkman, Lev M. (The World Bank, 2005)
The paper provides an empirical analysis of the determinants of fiscal decentralization within Russian regions in 1994-2001. The conventional view that more decentralized governments are found in regions and countries with higher income, higher ethnolinguistic fractionalization, and higher levels of democracy is not supported by the data. This motivates a more refined analysis of the determinants of decentralization that points to the link between decentralization and the structure of regional government revenue: access to windfall revenues leads to a more centralized governance structure. The degree of decentralization also depends positively on the level of urbanization and regional size and negatively on income and general regional development indicators such as the education level